ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL - Hermaya Ompusunggu, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
The objective of this research is to determine the effect of growth of sales, profitability, assets structure and firm size to capital structure. Data used in this research wre secondary data from manufacturing in various industry sector company”s financial statements in Indonesia Stock Exchange on the year of 2011-2014. The analysis method used is multiple linear regression, F test and T test. The result of the partially research /T test showed profitability and assets structure effect on capital structure. While the results of the simultaneous research/ F test showed variable growth of sales, profitability, assets structure and firm size effect on capital structure. The influence is 0,390 0r 39% the other 61% influenced by another varibale.